TANTANGAN DAN PELUANG BRICK AND MORTAR RETAIL DI ERA E-COMMERCE - Michael Kristanto (Akubis : Jurnal Akuntansi dan Bisnis, 2019)
In this modern days, E-commerce having a rapid growth and becoming an important activity. E-commerce is widely considered the buying and selling of products over the internet. With a broadening product range, E-commerce will have a direct effect on bricks and mortar retail. Now the business is moving into this new services, and it will reduce net demand for future additional retail space. The paper concludes that E-commerce will have significant impacts on Bricks and Mortar Retail. Kata Kunci: E-commerce, Bricks and Mortar Retail, direct effect, product